Maturity and Readiness Model for Industry 4.0 Strategy - Akdil, Kartal Yagiz; Ustundag, Alp; Cevikcan, Emre (Springer International Publishing, 2017)
Companies that transform their businesses and operations regarding to Industry 4.0 principles face complex processes and high budgets due to dependent technologies that effect process inputs and outputs. In addition, since Industry 4.0 transformation creates a change in a business manner and value proposition , it becomes highly important concept that requires support of top management for the projects and investments. Therefore, it requires a broad perspective on the company’s strategy, organization, operations and products. So, the maturity model is suitable for companies planning to transform their businesses and operations for Industry 4.0. It is a very important technique for Industry 4.0 in terms of companies seeking for assessing their processes, products and organizations and understanding their maturity level. In this chapter, existing maturity models for Industry 4.0 transformation are reviewed and a new Industry 4.0 maturity model is proposed.